Wanci dan Binongko sebagai Dialek yang Berkerabat dalam Bahasa Wakatobi - Nila Puspita Sari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
Sound change happens in a language even a dialect sincronically or diachronically will create one or more language or dialect variations. This study aims at:1) to determine the relationship between Wanci and Binongko dialect, 2) to descibe lingistic eviedences which suppoort act of determining the relationship between those dialect. This study is a dialectology research by using quantitative and qualitative method. The source of data in this study was based on field data by doing a direct interview to 487 basic words, 37 possessive phrases dan 16 both transitive and question clauses. The end of this research shows that based on statistic measure by using dialectometry, Wanci and Binongko isolects have relationship in sub-dialect level with percentage about 46.65%. Besides, qualitative analysis by identifying retention and innovation in linguistics features, there is no significant differences between those sub-dialects. Furthermore, linguistics features, they are phonology, morphology and syntax can be applied as evidence in determining the relationship between or among dialects and sub-dialects.